Depth probing soft x-ray microprobe (dpsxrm) for high resolution probing of earth’s microstructural samples (2016)
The Cambrian explosion: occurrence of landslides in very dry weather conditions: rockslides; dead, shriveled- up and crumbled leaves possessing fossil records with the semblance of well preserved, flat leaves: abundance of trilobite tracks in lower and higher rock layers: and sailing stones are enigmas demanding demystifications. These enigmas could be elucidated when data on soil structure, texture and strength are provided by some device with submicrometre accuracy; for these and other reasons, the design of a Depth Probing Soft X-ray Microprobe (DPSXRM), constituting a rotating X-ray window is being proposed; it is expected to deliver soft X- rays, at spatial resolution, Ω 600nm and to probe at the depth of 0.5m in 17s. Assessing subsurface stratigraphy is possible with the DPSXRM. The microprobe is portable comparedfo a synchrotron radiation facility (Diamond Light Source has land size of 43,300m* 2); spatial resolution,'q > 600nm, of the DPSXRM surpasses those of the X-ray Fluorescence microanalysis(lOpm), electron microprobe (I-3pm), and ion microprobe (5->30pm); the DPSXRM has allowance for multiple targets. Amongst other major optical components, a Fresnel Zone Plate (FZP) and Rotating X-ray Window are incorporated into the design to ensure that the desired image resolution is achievable and that the X-ray window membrane material survives the heat flux importation on it. Reflecting, refracting, diffracting and (or) absorbing optics areddentified as techniques needed to achieve this resolution. Vanadium and Manganese membranes are proposed owing to respective 4.952KeV VKa, and\ 5.899KeV MnKai X-rays emitted, which best suits micro-probing of Earth's microstructural samples. Compound systems like the Kirk-Patrick and Baez, electromagnetic lenses, small apertures and Abbe sine condition are considered to reduce or remove astigmatism and coma and spherical aberrations—leading to good image quality. Results are presented alongside, and relevant graphs are plotted. Magnification values of - 1.5 ≤ M ≤ 1.5, at - 70° ≤ θ ≤ 75° when - 30° ≤ θ ≤ 30° satisfied Abbe Sine Condition. The nth zone radius increases with the distance of separation of the DPSXRM’s electron gun and the zone plate. 5.899KeV MnKat and 4.952KeV VKa soft X-rays will travel a distance of 2. 75mm to form circular patches of radii 2.2mm and 2.95mm respectively. Zone plate with nth zone radius of 1.5mm must be positioned 1.5mm and 2 mm from the electron gun if circular patches must be formed from 4.952KeV VKat and 5.899KeV MnKajSoft X-rays respectively. The focal lengths of 0.25µm < F < 1.50µm and 0.04µm < F < 0.2µm covered by 4.952KeV VKat and\ 5.899KeV Mn Kat soft X-Rays, will occupy circular patch of area 0.03 mm2 < A < 0.2 mm2 respectively. The spatial resolution of 244nm < ς < 1460nm is attainable forfocal lengths of 38.1nm < F < 229nm and 32.0 nm < F < 1460192nm covered by 5.899KeV Mn Ka, and 4.952KeV VKa soft X-rays, respectively. Simulation results from COMSOL Multiphysics software uncover some deformations in Vanadium and Manganese microstructures.